Práticas de sustentabilidade relacionadas a materiais de consumo e compras e contratações sustentáveis relativos aos planos de logística sustentável: uma investigação sobre a Rede Federal de Educação Profissional, Científica e Tecnológica - BYRON MARIANO DE OLIVEIRA (2023)
The Federal Network of Professional, Scientific and Technological Education promotes and socializes knowledge, through teaching, research, extension and innovation, as well as environmental education, in light of the dimensions of sustainability. In the institutes of the Federal Network, there is consumption of various types of materials, as well as purchases and contracts inherent in the course of their activities, which entail negative environmental externalities. In order to mitigate the negative socio-environmental impacts they produce, Brazilian public agencies, such as the Federal Network, must comply with the precepts of Normative Instruction 10/2012 (IN 10/2012), which defines the rules for the preparation and publicity of Sustainable Logistics Management Plans (PLS). In the context of IN 10/2012, 7 minimum topics to be addressed in the PLS are defined, including: I) Consumables; and VI) Sustainable Purchasing and Contracting. Thus, the opportunity arises to ask: how do the Federal Network of Professional, Scientific and Technological Education's managers deal with the legal compliance of the Sustainable Logistics Management Plan? From this perspective, the general objective of this study was to evaluate the legal compliance of the implementation of the Sustainable Logistics Management Plan, within the scope of the Federal Network of Professional, Scientific and Technological Education. Specifically, the objective was to verify the compliance with Normative Instruction No. 10/2012 regarding the preparation, implementation and dissemination of the Sustainable Logistics Management Plan, Action Plan, and Monitoring Report, by the Federal Network of Professional, Scientific and Technological Education; to describe the actions aimed at the minimum topics of Consumable Materials and Sustainable Purchasing and Contracting, contained in the Sustainable Logistics Management Plans, of the Federal Network of Professional, Scientific and Technological Education; and to propose continuous improvements of actions on the management of minimum topics of Consumable Materials, as well as Sustainable Purchasing and Contracting, to be inserted in the next Action Plans, of the Sustainable Logistics Management Plan, of the Federal Institute of Mato Grosso do Sul. The study became exploratory, applied, qualitative and descriptive research. For the elaboration of the theoretical foundation, bibliographical research was carried out in the Scopus database. There was also a search for specific studies related to compliance with IN 10/2012 and practical compliance with the PLS. Research was also carried out on specific legislation for the elaboration of the legal basis. The collection of secondary data took place on the official websites of 41 institutes of the Federal Network, in October 2022. The results showed that when considering only the PLS and PA, 17% of the Federal Network complied with IN 10/2012, presenting PLS and PA in force; of the 83% that did not comply with this regulation, 27% had already prepared their PLS, but they are out of date, and 56% of the Federal Institutes did not present any document. And when the mandatory RA document is also considered, only 9.75% of the Federal Network is complying with IN 10/2012. Another 9.75% of the FI have already submitted reports from previous years, and 80.5% of the FI have never prepared any AR. This demonstrates a very low level of concern, with regard to meeting the dimensions of sustainability, by the institutions that have, by obligation, to promote and socialize knowledge, as well as environmental education, in light of these dimensions. Likewise, it showed non-observance on the part of the IF, including the IFMS, regarding compliance with IN 10/2012, a law that obliges all public administration agencies to prepare, implement and disclose their PLS. For future studies, it is recommended to investigate the other minimum topics (Electric Energy; Water and Sewage; Selective Collection, Quality of Life at Work, and Personnel Displacement) along with the Federal Network. Also, considering the low rate of compliance of IFs with IN 10/2012, it is recommended research that seeks to find out which ways the Public Administration could promote and encourage the implementation of the PLS in the Federal Network.